PENINGKATAN PENGETAHUAN DAN SIKAP PASANGAN USIA SUBUR DALAM KEIKUTSERTAAN BER-KB MELALUI LEAFLET - Erni Gustina; Puput Dwi Hastuti Retnosari; Risma Elfariyani Duwila; Lailatul Azizah; Tika Rastya Ningsih; Rosita Rosita (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The use of contraception is influenced by many factors such as knowledge, husband's support, culture, level of welfare, communication, information, and education. The purpose of this activity is to increase knowledge and attitudes of couples of reproductive age in participating in family planning. The method of service activities is the provision of direct intervention using leaflet media as a method of health education. The intervention was carried out for 2 days to 29 people. Provision of intervention to couples of reproductive age went well. Statistical test results for average knowledge (Mean = 9.00; 95% CI = -0.75-18.75; sig = 0.07) and attitude (Mean = 6.207; 95% CI = 2.09-10.3; sig = 0.005). There was increased in attitude before and after the provision of intervention through the media leaflet with participation in family planning. There were differences in the average couples of reproductive age knowledge before and after the providing of the intervention using leaflet media, but it was not statistically significant.